Interventions on the text of Novalis’ Journal in the original 1846 edition - Alberti, Miguel (Cuadernos de Ilustración y Romanticismo, 2025)
The text of Novalis’s private diary from mid-1797 was first published in 1846 with significant modifications made by the editor, Eduard von Bülow. This article examines these modifications and aims to provide some evidence that they were generally intended to shape the text in such a way as to present Novalis as a poet incapable of experiencing not only improper emotions or sensations but also tranquility or relief during his grieving process over the death of his fiancée, Sophie von Kühn. The analysis considers the full range of editorial operations carried out by Bülow, with particular focus on two aspects: first, the passages in which a deliberate effort to remove specific information from the diary can be observed, and second, the treatment of the enigmatic «determination» to which Novalis refers —an element that has given rise to various interpretations and remains a subject of debate today.